Research on tapering to elite female race walking players with altitude training characteristics - Zhu, N.; Tang, Q.; Li, X. (Exercise Biochemistry Review, 2018)
Objective The ultimate goal of athletic training is to perform the optimum competitive states in the competitions. The research has shown that one of the key factors to achieve the goal is effective and appropriate Tapering in preparing period. By systematically and completely tracing and summarizing the Tapering in endurance events with altitude training at the entire training period which could provide a better guidance for the training and bring into an furthest effects, providing a real reference cases for achieving competitive targets and scientific training.